Campus-Based Financial Aid Programs: Trends and Alternative Allocation Strategies. (June 2017) - Kelchen, Robert
Two federal campus-based financial aid programs, the Supplemental Educational Opportunity Grant (SEOG) and the Federal Work-Study Program (FWS), combine to provide nearly US2 billion in funding to students with financial need. However, the allocation formulas have changed little since 1965, resulting in community colleges and newer institutions getting much smaller awards than long-standing private colleges with high costs of attendance. I document the trends in campus-level allocations over the past two decades and explore several different methods to reallocate funds based on current financial need while limiting the influence of high-tuition colleges.